New physics from warped compact extra dimensions: from model building to colliders signals - Oliveira, Alexandra Carvalho Antunes de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The Higgs field of the Standard Model theory for elementary particles and interactions can be realized as a composite state from an underlying strong sector. Such hypothesis is very attractive as an ultraviolet completion of the Standard Model since it solves the hierarchy and avoids naturalness problems. The standard perturbative methods cannot be used in the context of strongly interacting theories, however thyose can be broadly describes in terms of extra dimensional models of gravity. We focus on the case of one additional Warped compact Extra Dimension (WED). The generic signatures of this scenario are the manifestation of heavy gravity particles, associated with the five dimensional metric, that couples with the Standard Model matter leading to direct collider signatures. The heavy gravity particles couples to the Higgs sector. The Higgs discovery had oponed a new investigation channel to LHC direct detection that is the di-higgs final state. We use Monte Carlo techniques to study the analysis strategies that would lead to a best recognition of new resonances decaying to a pair of higgses in hadron colliders, that can be interprets as the gravity particles. We finally present resonance searches performed with data taken by the CMS experiment on the 8 TeV LHC run. The results are interpreted as the gravity particles signatures in the WED context

No Modelo Padrão que descreve a física das partículas elementares e suas interações o campo de Higgs pode ser imaginado como um campo composto formado por uma força forte ainda desconhecida. Tal hípótese é bastante atrativa para completar o Modelo Padrão a altas energias. Problemas como hierarquia e naturalidade podem ser mais facilmente evitados. No contexto de uma força forte porém métodos de cálculo baseados em expansões perturbativas não tem mais validade. Uma alternativa para entender as propriedades básicas desse tipo de teoria é trabalhar em termos de teorias de gravitacão com dimensões extras. Nesta tese focamos no caso de uma dimensão espacial extra. Características genéricas desse tipo de cenário são a existência de partículas de gravidade massivas, associadas com a métrica penta-dimensional que acopla com o Modelo Padrão para matéria, levando a assinaturas diretas em colisores de partículas (como o LHC no CERN). Tais partículas de gravidade se acoplam com o setor de Higgs. A descoberta do bóson de higgs abriu um novo camp o de investigação para sua detecção direta, no estado final com dois bósons de higgs. Nós usamos técnicas de Monte Carlo para estudar as estratégias de análise que levariam a um melhor reconhecimento de novas ressonâncias que decaem em pares de bósons de higgs em colisores hadrônicos, que podem ser interpretadas como partículas de gravidade massivas. Finalmente apresentamos as buscas experimentais por tais ressonâncias realizadas no contexto do experimento CMS com dados retirados do primeiro run do LHC (com uma energia de centro de massa de 8 TeV)
Keywords: Modelo padrão (Física nuclear); Gravidade quântica; Standard model (Nuclear physics)